Performance measures for small-bowel endoscopy: a European Society of Gastrointestinal Endoscopy (ESGE) Quality Improvement Initiative - Spada, Cristiano; McNamara, Deirdre; Despott, Edward J.; Adler, Samuel; Cash, Brooks D.; Fernández-Urién, Ignacio; Ivekovic, Hrvoje; Keuchel, Martin; McAlindon, Mark; Saurin, Jean-Christophe; Panter, Simon; Bellisario, Cristina; Minozzi, Silvia; Senore, Carlo; Bennett, Cathy; Bretthauer, Michael; Dinis-Ribeiro, Mario; Domagk, Dirk; Hassan, Cesare; Kaminski, Michal F.; Rees, Colin J.; Valori, Roland; Bisschops, Raf; Rutter, Matthew D. (Endoscopy, 2019)
The European Society of Gastrointestinal Endoscopy (ESGE) together with the United European Gastroenterology (UEG) recently developed a short list of performance measures for small-bowel endoscopy (i. e. small-bowel capsule endoscopy and device-assisted enteroscopy) with the final goal of providing endoscopy services across Europe with a tool for quality improvement. Six key performance measures for both small-bowel capsule endoscopy and for device-assisted enteroscopy were selected for inclusion, with the intention being that practice at both a service and endoscopist level should be evaluated against them. Other performance measures were considered to be less relevant, based on an assessment of their overall importance, scientific acceptability, and feasibility. Unlike lower and upper gastrointestinal endoscopy, where performance measures had already been identified, this is the first time that small-bowel endoscopy quality measures have been proposed.